Borrowing Technique as Reflected in the Rainbow Rowell’s Novel “Fangirl” - Fristzy Claudia Permatasari (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
This research aims at describing the types of borrowing technique in the novel “Fangirl” by Rainbow Rowell, describing the dominant type of borrowing technique, describing the dominant word of borrowing technique, found the literature meaning in the borrowing word and found the implementation of borrowing technique in teaching translation. This research applied the qualitative research method by using content analysis research design. The data of this research were collected manually from the Novel “Fangirl” by Rainbow Rowell. The data found in the novel are pure borrowing and naturalized borrowing, the researcher then serve into tables. The researcher became the main instrument of this research. The procedures in analyzing the data were collecting, classifying, analyzing, discussing, and reporting the data. The result of this research shows that there are two borrowing technique namely naturalized borrowing and pure borrowing are the types the researcher found in the novel and the researcher explained each word as a borrowing technique in the novel using literature meaning. Also, from the result it shows that the dominant type is represented by the naturalized borrowing. This is indicated in quantitative terms by 51,2% for the naturalized borrowing in contrast to 48,8% for the pure borrowing. The word “dad” from pure borrowing is the dominant word that has been found in the novel “Fangirl”. The borrowing technique is the easily technique that can help the teacher to teach translation to the student.